Surface science goes liquid ! - Steinrück, Hans-Peter (Surface Science, 2010)
Ionic liquids are a new class of materials with most interesting properties. They are liquid at room temperature, but have a negligible vapour pressure. Consequently they can, in contrast to normal liquids, be investigated by all UHV-based methods of surface science. This allows to determine their properties with the same atomic level accuracy that is presently common for solid surfaces and conventional adsorbate systems. Apart from the investigation of the specific properties of ionic liquids, which are relevant for many applications, this also opens the possibility to obtain more detailed insight in the general physical and chemical properties of liquids. In that sense it opens the door to a new chapter of surface science - "Ionic Liquid Surface Science". © 2010 Elsevier B.V. All rights reserved.